A Rare Case of Orthostasis, Dizziness, and Non-O1, Non-O139 Vibrio cholerae Infection in a Lung Transplant Recipient - Michael T. Olson; Tejus Walia; Satish Chandrashekaran; Sreeja Biswas Roy; Ashwini Arjuna (Case Reports in Transplantation)
Non-O1, non-O139 Vibrio cholerae are rare strains that are generally nonpathogenic in immunocompetent hosts. However, this pathogen has been shown to cause gastroenteritis, wound infections, or bacteremia in immunocompromised patients and is associated with significant mortality in these hosts. Herein, we describe a case of hemorrhagic enterocolitis in a lung transplant recipient with an atypical presentation of non-O1, non-O139 V. cholerae and ongoing orthostasis. The patient reported recent seafood consumption and was managed appropriately with antibiotic therapy before necessitating esophagogastroduodenoscopy (EGD) for further objective testing.